Omental Tissue-Mediated Tumorigenesis of Gastric Cancer Peritoneal Metastases - Kersy, Olga; Loewenstein, Shelly; Lubezky, Nir; Sher, Osnat; Simon, Natalie B.; Klausner, Joseph M.; Lahat, Guy (Frontiers in Oncology, 2019)
The peritoneal cavity, especially the omentum, is a common site for gastric cancer metastasis, representing advanced disease stage and poor prognosis. Here we studied the effects of omental tissue on gastric cancer tumor progression in vitro and in vivo. Utilizing in vitro models, we found that omental tissue secreted factors increased gastric cancer cellular growth (by 30%-67%, P < 0.05), motility (> 8 fold, P < 0.05), invasiveness (> 7 fold, P < 0.05) and chemoresistance to platinum-based chemotherapeutic agents (>1.2-fold for oxaliplatin and >1.6-fold for cisplatin, P < 0.05). Using a robust proteomic approach, we identified numerous molecules secreted into the omental tissue conditioned medium (CM) which may promote gastric cancer cellular aggressiveness (i.e. IL-6, IL-8, MMP9, FN1 and CXCL-5). Next, an in vivo xenograft mouse model showed an increased human gastric adenocarcinoma tumor volume of cells co-cultured with human omental tissue secreted factors; 1.6±0.55 cm3 versus 0.3±0.19 cm3 (P < 0.001), as well as increased angiogenesis. Finally, exosomes were isolated from human omental tissue CM of gastric cancer patients. These exosomes were taken up by gastric cancer cells enhancing their growth (> 8 fold, P < 0.01) and invasiveness (> 8 fold, P < 0.001). Proteomic analysis of the content of these exosomes identified several established cancer- related proteins (i.e. IL-6, IL-8, ICAM-1, CCl2 and OSM). Taken together, our findings imply that the omentum play an active role in gastric cancer metastasis. The data also describe specific cytokines that are involved in this cross talk, and that omental tissue- derived exosomes may contribute to these unique cellular interactions with gastric cancer cells. Further studies aimed at understanding the biology of gastric cancer intra peritoneal spread are warranted. Hopefully, such data will enable to develop future novel therapeutic strategies for the treatment of metastatic gastric cancer.